Influence of a bifunctional linker on the loading of Cu2AgInS4 QDs onto porous TiO2 NFs to use as an efficient photoanode to boost the photoconversion efficiency of QDSCs. (22nd July 2020) - Kottayi, Roopakala; Panneerselvam, Pratheep; Singh, Nisha; Murugadoss, Vignesh; Sittaramane, Ramdasse; Angaiah, Subramania
Abstract : Quaternary Cu2 AgInS4 quantum dots anchored more onto porous TiO2 NFs through a linker, 3-mercaptopropionic acid exhibits higher photoconversion efficiency of QDSC than that of the same anchored without a linker. Abstract : In the present study, quaternary Cu2 AgInS4 quantum dots (CAIS QDs) are synthesized by a hot injection method. The crystallographic information of the QDs is confirmed by X-ray diffraction and high-resolution transmission electron microscopy studies. Energy dispersive X-ray spectrum analysis reveals a 1.93 : 1.0 : 1.01 : 3.80 elemental composition ratio of the synthesized QDs. X-ray photoelectron spectroscopy analysis confirms the oxidation states of the elements present in the synthesized QDs. The optical properties are studied using UV-VIS absorption spectroscopy and PL emission spectroscopy. From a Tauc plot, the bandgap of the synthesized QDs is calculated to be 1.6 eV. The synthesized QDs are used as sensitizers and are loaded onto P-TiO2 NFs using 3-mercaptopropionic acid as a bifunctional linker as well as without the use of a bifunctional linker. Quantum dot sensitized solar cells (QDSCs) are fabricated using Cu2 AgInS4 QD sensitized porous TiO2 NFs as the photoanode, Cu2 S as the counter electrode and polysulphide as the electrolyte, in order to study its photovoltaic performance. These results revealed that the QDs loaded onto the porous TiO2 NFs using a bifunctional linker exhibits 27% improvement in the photoconversion efficiency of QDSC than that of the QDs loaded onto the porous TiO2 NFs without the use of a bifunctional linker.